Հովհան Մայրագոմեցու «Վասն պատկերաց Եւ նկարագրութեանց» գրվածքի շուրջ - Անդրեաս վարդապետ Եզեկեան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Летописное наследие выдающегося богослова и духовного деятеля Армянской Церкви VII века Ована Майрагомеци дошло до нас в неполном виде. А в деле изучения сохраненных сочинений возникают сложности, так как авторство некоторых из них все еще ставится под сомнение, породив в научной сфере различные точки зрения. The literary legacy of Hovhan of Mayravank, prominent theologian and religious fi gure of the 7th century of the Armenian Church has reached us in a very incomplete condition. And the fact that the authorship of some of the preserved writings is still uncertain has caused diffi culties in studying them and led to various opinions.
Keywords: Literature